Aetiology and outcome of Hypernatremia in Post Diarrhoeal Acute Kidney Injury in Children An Experience in Dhaka Medical College Hospital (Northern International Medical College Journal, 2017)
Background : Hypernatremia (serum sodium 150mmol/L) is one of the most life-threatening complications of childhood diarrhoea, Acute kidney injury(AKI) when associated with hypernatremia results increased mortality and long term morbidity.Objectives : Our objective was to find out the aetiology and outcome of hypernatremia in post diarrhoeal AKI in children in a teaching hospital in Bangladesh.Methods : This prospective observational study was conducted over 06 months in the Paediatric Nephrology Department of Dhaka Medical College Hospital. A total of 15 children withpost diarrhoeal AKI withhypernatremia were evaluated.AKI staging was done by pRIFLE criteria. Hypernatremia was classified into mild, moderate and severe gradings. All patients were treated conservatively and with Intermittent Peritoneal Dialysis (IPD) as needed. Fluid adjustment was done according to serum sodium level.At the end of the study, samples were divided in to survive and death groups depending on outcome.Results : Age of the children ranged from 2 months to 18months. Ninety three percent cases were under 1 year.Forty seven percent patients were in Failure stage of AKI, 47%in Injury and 1 patient in Risk stage.Out of 15 cases 93% had severe hypernatremia. In 67% casesthe causes of hypernatremia were intake of concentrated oral rehydration solution (ORS) and found more in winter season. Regardless of cause overall 47% survived with normal renal functions and 53% died.Conclusion : Intake of concentrated ORS and diarrhoea during winter seasona are the most important cause of hypernatremia in infancy. Hypernatremia with AKI stage III (Failure) had poorest outcome.Northern International Medical College Journal Vol.8(2) January 2017: 224-227